A year of living kindly choices that will change your life and the world around you - Cameron, Donna (Tantor Audio, 2020)
Being kind is something most of us do when it's easy and when it suits us. Being kind when we don't feel like it, or when all of our buttons are being pushed, is hard. But that's also when it's most needed; that's when it can defuse anger and even violence, when it can restore civility in our personal and virtual interactions. Kindness has the power to profoundly change our relationships with other people and with ourselves. It can, in fact, change the world. In A Year of Living Kindly-using stories, observation, humor, and summaries of expert research-Donna Cameron shares her experience committing to 365 days of practicing kindness. She presents compelling research into the myriad benefits of kindness, including health, wealth, longevity, improved relationships, and personal and business success. She explores what a kind life entails, and what gets in the way of it. And she provides practical and experiential suggestions for how each of us can strengthen our kindness muscle so choosing a life of kindness becomes ever easier and more natural. An inspiring, practical guide that can help any listener make a commitment to kindness, A Year of Living Kindly shines a light on how we can create a better, safer, and more just world-and how you can be part of that transformation.